2022
DOI: 10.1002/adma.202200048
|View full text |Cite
|
Sign up to set email alerts
|

A Transformable Amphiphilic and Block Polymer−Dendron Conjugate for Enhanced Tumor Penetration and Retention with Cellular Homeostasis Perturbation via Membrane Flow

Abstract: An approach for stealthy-to-sticky transition of nanomedicines has been demonstrated to augment the therapeutic efficacy: the nanomedicines are nonsticky (or "stealthy") during circulation in the bloodstream, but become sticky at tumor sites for effective interaction with cell membranes during capillary extravasation and cellular internalization. [2] For example, the pH-triggered charge reversal of tumor microenvironment-responsive nanomedicines has been reported to facilitate extravasation and penetration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Previously, we have shown that the volume of the PPO block determines the extent of perturbation exerted by Pluronic insertion into the lipid bilayer . Gu et al showed the great potential for the embedding of a bulk hydrophobic amphiphile in the lipid portion of the cell membrane to cause a cascade of apoptosis-like intracellular events leading to cell death . We suggested that PPO blocks of Pluronics also trigger a set of intracellular reactions that finally disable MDR …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Previously, we have shown that the volume of the PPO block determines the extent of perturbation exerted by Pluronic insertion into the lipid bilayer . Gu et al showed the great potential for the embedding of a bulk hydrophobic amphiphile in the lipid portion of the cell membrane to cause a cascade of apoptosis-like intracellular events leading to cell death . We suggested that PPO blocks of Pluronics also trigger a set of intracellular reactions that finally disable MDR …”
Section: Resultsmentioning
confidence: 81%
“…7 Gu et al showed the great potential for the embedding of a bulk hydrophobic amphiphile in the lipid portion of the cell membrane to cause a cascade of apoptosislike intracellular events leading to cell death. 35 We suggested that PPO blocks of Pluronics also trigger a set of intracellular reactions that finally disable MDR. 4 PEG−Glycocalyx Interaction Enhances Cell Viability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The third permeation barrier is composed of densely packed BCa cell aggregates and a dense extracellular matrix. 5 , 23 , 24 The method by which intravesically administered drugs reach distant BCa cells solely depends on the direct penetration of drugs across the third permeation barrier in a layer-by-layer manner. 3 Multicellular spheroids (MCSs) have been proposed as an in vitro 3D-cultured tumor model to evaluate the tumor penetration of drugs.…”
Section: Resultsmentioning
confidence: 99%
“…7,[22][23][24] Also, among the recently investigated complexes displaying promising results as anticancer drugs, the ruthenium(II)-cyclopentadienyl complex [Ru(Z 5 -C 5 H 5 )(PPh 3 ) 2 Cl] (RuCp) tested in vitro by our group in a set of cancer cell lines showed promising activity. 15 Nanomaterials such as dendrimers 25,26 and derivatives [27][28][29][30] present desirable and attractive characteristics for application in the biomedical field. Dendrimers are monodispersed globular macromolecules that can be easily functionalized, and thus can act as a drug carrier and/or target chemical groups.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials such as dendrimers 25,26 and derivatives 27–30 present desirable and attractive characteristics for application in the biomedical field. Dendrimers are monodispersed globular macromolecules that can be easily functionalized, and thus can act as a drug carrier and/or target chemical groups.…”
Section: Introductionmentioning
confidence: 99%